PATOFISIOLOGI MIASTENIA GRAVIS - Devita Anggraeni Soeroso; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2023)
Myasthenia Gravis (MG) is an autoimmune disease that disrupts transmission at the neuromuscular junction (NMJ). In myasthenia gravis, the immune system will attack the acetylcholine receptor (AChR) or other proteins involved in neuromuscular transmission or due to abnormalities in the thymus, which plays a role in immunity. This causes characteristic manifestations in the form of muscle weakness, which will improve after rest. So, in its management, the use of immunosuppressive therapy and removal of the thymus can be a therapeutic option depending on the type and severity of the disease.